(untitled) (Indian Journal of Animal Production and Management, 2019)
The present study was carried out to know management of commercial and traditional goat farms in middle Gujarat. The data were collected from randomly selected nine goat farmers based on their flock strength. Among the nine goat farms, four farms were big with average flock strength of greater than 160 goats, whereas five farms were having a flock size of 20-25 goats. The large commercial goat farms reared mostly Sojat, Sirohi, Punjabi, Pateera, Totapuri and Jamunapari breed of goats. They kept only a few numbers of female animals where as male kids were purchased and reared for slaughter purpose. The owners of commercial goat farms maintained their goats under stall feeding and browsing. They allowed goats for browsing during morning for 2 to 5 hrs. In addition, goats were fed with concentrate about 500 gm/day along with mineral mixture. The owners of commercial farms reared goats more scientifically, with the regular deworming and vaccination. The farms generated an average profit of Rs. 5000/- per goat/annum. The traditional goat farms reared Surti, Marwari breeds mostly and non-descript breeds of goat. The goats maintained only on browsing while during shortage of fodder they offered 150 –200 gm concentrate to each goat per day. They reared mostly female goat earned profit through sale of milk and male kids. The average profit of farm was Rs. 2000/- per goat/annum. The incidence of kid mortality was higher in commercial goat farms (15.75%) as compared to traditional goat farms (8.90%) which may be due to large number of goat reared on commercial goat farms. The present study indicated that if farmers of traditional goat farms reared goats scientifically, then they can earn more profit. The commercial large goat farms need to be more intensive in the management to control kid mortality and improve their profit.